IMPLEMENTASI METODE SHOW AND TELL UNTUK MENINGKATKAN HASIL BELAJAR DAN KETERAMPILAN KOLABORASI DI SDN 1 KALIANYAR - Ela Nabilla; Khoimatun; Dede Hadiansah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on the fact that students' learning completion in PPKn lessons has not been maximized, there are 70% or 14 students who have not completed it. Because the teaching and learning process is more dominated by teachers, still using conventional models, namely lectures and practice questions. One of the things that is done is the renewal of learning methods that place students as the center of learning, one of which is using the Show and Tell method model and collaboration skills in PPKn Learning in everyday life. This study aims to determine the implementation of the Show and Tell method, to determine the improvement in PPKn learning outcomes and collaboration skills of grade IV students of SDN 1 Kalianyar with the implementation of the Show and Tell Method. The research method used is Classroom Action Research (CAR) with III cycles using the design model from Kemmis and MC Taggart which consists of four steps, namely: planning, implementation, observation, reflection. This research was applied to 20 grade IV students. The learning outcomes obtained during the implementation of the action increased as seen from the results of cycle III, as many as 18 students completed with a classical average of 81.8 and a percentage of 90%. Based on the results of the study, it shows that the Show and Tell method can improve learning outcomes and collaboration skills of elementary school students.